1998
DOI: 10.1063/1.122288
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of deformation-assisted crystallization in amorphous Fe78B13Si9

Abstract: Low-energy ball milling of amorphous Fe78B13Si9 has been performed at temperatures between 25 and 250 °C. Primary crystallization is observed after milling at elevated temperatures, but not after annealing at the same temperatures. Although milling at room temperature creates nucleation sites for primary crystallization, subsequent annealing at elevated temperature does not result in significant crystallization. Heating by ball impact and contamination by the milling tools during milling are ruled out as the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
40
1
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 18 publications
1
40
1
1
Order By: Relevance
“…Thermal annealing has been the typical method to induce nano-crystallites in an amorphous matrix [5][6][7][8]. However, since the first observation of the formation of Al nano-crystallites at shear bands of Al-based amorphous alloy ribbons bent at room temperature [9], it has been widely observed that nanocrystallization in an amorphous matrix can be induced by a variety of mechanical approaches, such as bending [9][10][11][12], nano-indentation [13,14], ball milling [15], tension [2,10], and even by hydrostatic pressure [16,17]. The temperature rise during mechanical processes was first noted as the reason for the crystallization in amorphous matrix [10,18].…”
Section: Introductionmentioning
confidence: 99%
“…Thermal annealing has been the typical method to induce nano-crystallites in an amorphous matrix [5][6][7][8]. However, since the first observation of the formation of Al nano-crystallites at shear bands of Al-based amorphous alloy ribbons bent at room temperature [9], it has been widely observed that nanocrystallization in an amorphous matrix can be induced by a variety of mechanical approaches, such as bending [9][10][11][12], nano-indentation [13,14], ball milling [15], tension [2,10], and even by hydrostatic pressure [16,17]. The temperature rise during mechanical processes was first noted as the reason for the crystallization in amorphous matrix [10,18].…”
Section: Introductionmentioning
confidence: 99%
“…Формирование нанокристаллов при пластической де-формации наблюдалось при разных способах дефор-мирования: изгибе [16], низкоэнергетическом размо-ле [17], наноиндентировании [18], холодной прокат-ке [19,20]. Особенно эффективными с точки зрения инициирования нанокристаллизации оказались мето-ды интенсивной пластической деформации, основным из которых является кручение под высоким давлени-ем [21][22][23][24][25][26][27].…”
Section: Introductionunclassified
“…Recently, mechanically induced nanocrystallization in amorphous alloys, achieved by ball milling, [1][2][3] bending, 4,5 rolling, 6 tension, 7,8 and nanoindentation, 9,10 has received much attention. The process of mechanically induced nanocrystallization is of potential practical significance for the synthesis of amorphous-nanocrystallite composites and their processing and service.…”
Section: Introductionmentioning
confidence: 99%
“…12 Mechanically induced nanocrystallization appears to be a general phenomenon, since it has been observed in Al-, Zr-, and Fe-based alloys. [1][2][3][4][5][6][7][8][9][10][11][12] However, this process is composition dependent; it may vary between otherwise similar alloys. 1,4 Mechanically induced nanocrystallization occurs exclusively at shear bands, which are the main microstructural response to plastic deformation in amorphous alloys.…”
Section: Introductionmentioning
confidence: 99%